Apoptotic Potential of Iloneoside from Gongronema latifolium Benth against Prostate Cancer Cells Using In Vitro and In Silico Approach - Gyebi, Gideon A.; Afolabi, Saheed O.; Ogunyemi, Oludare M.; Ibrahim, Ibrahim M.; Olorundare, Olufunke E.; Adebayo, Joseph O.; Koketsu, Mamoru (Cell biochemistry and biophysics, 2025)
Prostate cancer is a major cause of cancer-related mortality in men worldwide. The anti-proliferative activity of Gongronema latifolium leaf extracts on some cancer cells has been reported. Herein, we investigated the growth inhibitory effect of the Gongronema latilolium leaf methanol extract and isolated pregnane (iloneoside) against prostate cancer cell lines using the MTT cell proliferation assay, apoptosis quantification, cell cycle analysis using flow cytometry and computational analysis molecular docking, molecular dynamics simulation (MDs), binding free energy computation and cluster analysis. In addition, UPLC-ESI-TOFMS chemical fingerprinting of previously isolated compounds was performed. The extract inhibited the growth of the cell lines with an IC 50 of 49.3 µg/ml and 28.4 µg/ml for 24 h and 48 h, respectively, for PC3; and 43.7 µg/ml and 22.3 µg/ml for 24 h and 48 h, respectively, for DU145. Iloneoside demonstrated low inhibitory activities against PC3 and DU145 (IC 50 > 80 μM). Apoptotic quantification and cell cycle analysis further showed that iloneoside induced apoptosis in a few cells at a dose of 200 uM. The ensemble-based molecular docking of the iloneoside to BCL-XL and BCL-2 proteins, and docking to MCL-1, BCL-A1 and BFL-1 proteins, respectively, presented binding energies of −7.22 ± 0.5, −8.12 ± 0.55, −7.1, −7.2 and −6.3 kcal/mol, while the MM/PBSA binding free energy was −25.72 ± 7.22 and −27.76 ± 11.32 kcal/mol for BCL-XL and BCL-2 proteins. Furthermore, iloneoside was stable during the 100 ns MDs analysis, while the clustering of the MDs trajectories showed that the interactions were strongly preserved. Iloneoside, in part, or in synergy with other constituents, may be responsible for the antiproliferative activities of the leaf, subject to further investigation.